A relação entre a irradiação transcutânea do sangue – ILIB modificada e os níveis de cortisol salivar em cuidadores de idosos saudáveis - (:unkn) unknown (Universidade Brasil, 2021)
Formal caregivers usually have exhaustive work scale that can trigger emotional changes and a decrease in the quality of life of these professionals. The use of ILIB (Intravascular Laser Irradiation of Blood) can improve the immunological activity of the blood, in addition to facilitating blood circulation and has been used in the treatment of different diseases. The aim of this study was to verify the effects of ILIB, applied transcutaneous, in relation to the levels of salivary cortisol of caregivers of formal elderly in long-term care institutions, who work during the day and night. Forty-two caregivers of formal elderly people were divided into 6 groups: Day Group (DG) (n=7); Day ILIB Group (DILIBG) (n=7); Day ILIB/placebo group (DPG) (n=7); Night Group (NG) (n=7); ILIB Night Group (NILIBG) (n=7); and Night ILIB/placebo Group (NPG) (n=7). Volunteers in the ILIB and ILIB / placebo groups received ILIB, in the radial artery region, by means of a low-power laser (Laser Duo, MMOPTICS, São Carlos, Brazil), l= 660 nm, P = 100 mW / 30 min, every other day, for 2 weeks, totaling 8 sessions of treatment/placebo, while the groups: GD and GN performed salivary collection on the day off and on the workday. All participants answered the quality of life questionnaire (QLQ) before any procedure and saliva collections for volunteers in the ILIB and ILIB/placebo groups were performed before any procedure; 24 h and 48 h after 8 treatment/placebo sessions, while the groups: DN and NG performed salivary collection on the day off and on the workday. The QLQ results did not show statistically significant differences between daytime and nighttime workers (p>0.05). Regarding cortisol quantification, the results showed statistically significant decreases (p<0.05) in salivary cortisol levels, both in the ILIB groups and in the placebo groups. Therefore, we can conclude that it was possible to measure the salivary cortisol levels of caregivers of formal elderly in long-stay institutions, who work day and night, treated or not with ILIB. However, ILIB cannot help to reduce salivary cortisol levels in caregivers of elderly people in long-term care facilities.
Keywords: Fotobiomodulação; Irradiação transcutânea; ILIB - Intravascular Laser Irradiation of Blood; Luz Laser sobre o Sangue; Bioengenharia